A Retrospective Analysis of Gabapentinoid and Opioids to Opioid Monotherapy for Pain Relief in Patients with Chronic Neck and Low Back Pain - Knezevic, Nebojsa Nick; Aijaz, Tabish; Camacho-Ortega, Alvaro; Candido, Kenneth D (Pain medicine (Malden, Mass.), 2021)
Abstract Objective We compared the reduction in pain and opioid consumption in patients with chronic spinal pain on concomitant gabapentinoids and opioids with patients using opioids only. Design This was a retrospective chart review of patients with chronic neck or low back pain who were on opioids with at least a 24-month follow-up. Setting Single-center pain clinic in an urban setting. Subjects 167 patients with chronic spinal pain lasting at least six months. Methods Patients on gabapentin or pregabalin were included in the gabapentinoid group, while the other patients were included in the non-gabapentinoid group. Primary outcome was assessment of pain scores measured via a numeric rating scale (NRS), and secondary outcomes were response to the treatment (>2 point reduction on NRS) and daily opioid use measured in morphine milliequivalents. Results Pain scores were reduced in the first six months and plateaued after that in both groups. At the end of 24 months, the average pain score was 6.71 in the gabapentinoid group, while the average pain score was 7.18 in the non-gabapentinoid group. There was no statistical significance between the groups (p = 0.28). There was no difference in response to treatment in gabapentinoid group (33.3%) when compared with non-gabapentinoid group (32.7%). We also failed to find any significant difference in daily opioid usage between the two groups. Conclusion Gabapentinoids may not lead to reduction in pain or opioid consumption in patients with chronic spinal pain. A careful approach must be adopted while prescribing gabapentinoids in the chronic spinal pain patient population.